The impact of Research and Innovation Investment on Bank’s financial performance: A study on Mutual Trust Bank Limited, Bangladesh - Yeasin, Hossain Mohammad (Brac University, 2023)
This research report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2022.